EVALUASI PROGRAM PEMBANGUNAN DI KOTA TERPADU MANDIRI TELANG KABUPATEN BANYUASIN - Habena, Ahmad Ridhuan (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
This study examines how the Evaluation of Integrated Urban Development Programme in Independent Telang Banyuasin. The research variables consisted of contex, input, process and product.Design analysis using descriptive analysis method which is carried out through several stages: data reduction, conclusion and verification. With the unit of analysis of Manpower and Transmigration Banyuasin. Data were collected through library research, observation and interviews. Results of the study revealed that with the support of government Banyuasin for basic infrastructure development with empowerment of communities the KTM Telang is able to carry its potenty that district make it to be the new center of  economy, the centeroy government administration, and speed the overall regional development. Disnakertrans Banyuasin is supported by 83 employees who are dominated by groups of the structural power. The composition of employees in terms of level of education, can be quite adequate, since most is a degree with strata 1 to strata 2. Sources of state budget funds amounting to Rp. 3.3 billion, -. In transport infrastructure since the year 2008 up to now has been absorbing the budget either through APBN and APBD Banyuasin outside the Central Budget and province are as follows covering Management Office, Building Business, Markets, Smart Houses, mosques and house Jaga, Islamic Center, Parks cities and Tugu KTM, Roads and Bridges concrete Pier concrete and office space, the Network for Clean Water, Electricity Network and Street Lights, Buildings Rice Milling Plane (RPM), House Wira Business, Building RO system, Gate KTM and Regions Seed Center. Telang KTM development program which is managed by Disnakertrans Banyuasin has not been maximized to various constraints faced such as lach of quality human resources and inadequate budget. In the future, the work program Disnakertrans still need to be organized better. Some things need attention to be followed all the parties in the development of KTM Telang: Need Improvement, Development Implementation Coordination and synchronization of all stakeholders related sectors location with Village Center Zone KTM KTM. Programs and Activities Implementation of Physical Development of 2020 has been implemented in accordance with the target. Regional Development Action Plan 2021 KTM Telang directed, among others, for the construction of roads, improvement of roads, construction of buildings, renovation of buildings, the installation of water pipes clean.